Role of salivary epithelial toll‐like receptors 2 and 4 in modulating innate immune responses in chronic periodontitis. (17th May 2013) - Swaminathan, V.; Prakasam, S.; Puri, V.; Srinivasan, M.
Abstract : Background and Objective: Chronic periodontitis is initiated by sequential colonization with a broad array of bacteria and is perpetuated by an immune‐inflammatory response to the changing biofilm. Host recognition of microbes is largely mediated by toll‐like receptors (TLRs), which interact with conserved pathogen‐associated molecular patterns. Based on ligand recognition, TLR‐2 and TLR‐4 interact with most periodontal pathogens. Extracrevicular bacterial reservoirs, such as the oral epithelial cells, contribute to the persistence of periodontitis. Human saliva is a rich source of oral epithelial cells that express functional TLRs. In this study we investigated the role of salivary epithelial cell (SEC) TLR‐2 and TLR‐4 in patients with generalized chronic periodontitis. Material and Methods: Unstimulated whole saliva (UWS) was collected from patients with generalized chronic periodontitis and from healthy individuals after obtaining informed consent. Epithelial cells isolated from each UWS sample were assessed for TLR‐2, TLR‐4, peptidoglycan recognition protein (PGRP)‐3 and PGRP‐4 by quantitative real‐time PCR. In addition, the SECs were stimulated in vitro with microbial products for up to 24 h. The culture supernatant was assessed for cytokines by ELISA. Results: Stimulation with TLR‐2‐ or TLR‐4‐specific ligands induced cytokine secretion with differential kinetics and up‐regulated TLR 2 and TLR4 mRNAs, respectively, in cultures of SECs from patients with periodontitis. In addition, the SECs from patients with periodontitis exhibited reduced PGRP3 and PGRP4 mRNAs, the TLR‐responsive genes with antibacterial properties. Conclusion: SECs derived from the UWS of patients with chronic periodontitis are phenotypically distinct and could represent potential resources for assessing the epithelial responses to periodontal pathogens in the course of disease progression and persistence.